1998
DOI: 10.3109/08880019809028790
|View full text |Cite
|
Sign up to set email alerts
|

Genotype-Phenotype Correlation of Sickle Cell Disease in the United Arab Emirates

Abstract: We have identified the beta s-globin gene haplotypes of 85 patients with sickle cell disease attending the Dubai Thalassemia Center and assessed the influence of haplotype, alpha-thalassemia, and fetal hemoglobin on the clinical presentation. Identification of the beta s haplotypes was based on mutation analyses in the promoter sequences of the G gamma- and A gamma-globin genes. The Arabian-Indian haplotype was found in 52% of the beta s chromosomes, whereas the remaining were the Bantu and Benin haplotypes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Wide variations were reported in the clinical features ranging from moderate to a severe disease, with elevated Hb F levels and associated α-thalassaemia4447–49. Other investigators4850 showed the presence of Saudi-Indian haplotype in 52 per cent of the β S chromosomes that was concurrent with the mild form of the disease.…”
Section: Frequency and Distribution Of Sickle Cell Gene Among Arabsmentioning
confidence: 90%
See 1 more Smart Citation
“…Wide variations were reported in the clinical features ranging from moderate to a severe disease, with elevated Hb F levels and associated α-thalassaemia4447–49. Other investigators4850 showed the presence of Saudi-Indian haplotype in 52 per cent of the β S chromosomes that was concurrent with the mild form of the disease.…”
Section: Frequency and Distribution Of Sickle Cell Gene Among Arabsmentioning
confidence: 90%
“…In Arabian Peninsula; Bahrain, UAE, Oman, Kuwait, and Qatar, the disease is generally mild with a mild to moderate anaemia and a few complications, though some patients have a severe disease requiring regular blood transfusions and hospitalization3339404854. In Saudi Arabia, the eastern province shows similar mild pattern, while in the western part of the country, along the Red Sea, and Yemen, the severe pattern predominates1628.…”
Section: Clinical Presentation Of Scdmentioning
confidence: 99%
“…Oman is unique in the Arabian Peninsula; the BEN, AI, and Bantu (BAN) haplotypes are encountered frequently because of their geopolitical history and early migrations/interactions . Most patients with SCD in the United Arab Emirates also carry the AI haplotype, although both the BEN and BAN are also encountered with less frequencies …”
Section: Classification Of Tammv Values Reported From Different Countmentioning
confidence: 99%
“…It is a major genetic factor in a group of patients with co-inherited S ␤ -thalassemia genotype. Our DNA-based studies demonstrated that the ␤ S gene is indeed the second most common ␤ -globin gene defect in the UAE [2] . In addition HbE is also present particularly in the expatriate community from Bangladesh.…”
Section: Introductionmentioning
confidence: 99%